2023
DOI: 10.3390/polym15173578
|View full text |Cite
|
Sign up to set email alerts
|

Formation of Hydrophobic–Hydrophilic Associates in the N-Vinylpyrrolidone and Vinyl Propyl Ether Copolymer Aqueous Solutions

Sherniyaz Kabdushev,
Grigoriy Mun,
Ibragim Suleimenov
et al.

Abstract: Utilizing turbidimetry data, an examination is conducted on the behavior of solutions containing N-vinylpyrrolidone and vinyl propyl ether copolymer within a temperature range coinciding with the occurrence of a phase transition. The investigation reveals that within specific conditions prevailing in this domain, the emergence of entities denoted as hydrophobic–hydrophilic associates is conceivable. These entities are characterized by the presence of a relatively dense core, upheld by hydrophobic interplays, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
21
1

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(22 citation statements)
references
References 52 publications
(84 reference statements)
0
21
1
Order By: Relevance
“…The curves presented in Figure 1 and Figure 2 do not meet this criterion. As the temperature increases, they do not reach a plateau, as is characteristic of the curves studied in the cited works [ 46 , 53 ].…”
Section: Discussionmentioning
confidence: 77%
See 4 more Smart Citations
“…The curves presented in Figure 1 and Figure 2 do not meet this criterion. As the temperature increases, they do not reach a plateau, as is characteristic of the curves studied in the cited works [ 46 , 53 ].…”
Section: Discussionmentioning
confidence: 77%
“…We emphasize that the phase portrait method has been proposed in our works and is still mainly used by our research group [ 46 , 53 ]. In this and our previous work, it is shown that our proposed method allows us to obtain non-trivial information about the nature of phase transitions.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations